Effects of shoulder stability on endpoint stiffness. - Perreault, E.J.
Considers how unconstrained trunk and shoulder movements influence the control of arm mechanics. The goal of this study was to determine how the net mechanical properties of the endpoint of the arm are affected by changes in trunk support. Specifically, the authors examined endpoint stiffness properties. Endpoint stiffness describes the relationship between externally imposed displacements of the arm, as measured at the hand, and the endpoint forces required to effect those displacements. It quantitatively describes the mechanical interface that the arm presents to its environment, and thus it is thought to play a crucial role in the control of posture and movement. The authors estimated endpoint stiffness when the trunk and shoulder girdle were restrained and when they were free to move. In addition, they developed a system identification algorithm that allows them to estimate the contributions of the arm stiffness (equivalent to constrained conditions) to the net endpoint stiffness during unconstrained tasks. The authors' results show that although endpoint stiffness decreased with increased trunk and shoulder girdle mobility, the contributions of the elbow muscles to this net endpoint stiffness remains invariant with respect to changes in restraint. These results imply that the neuromotor system regulates arm stiffness independently from trunk and shoulder girdle stiffness, thereby providing a simplified control strategy for the generation of endpoint stiffness properties.
Keywords: Arm mechanics; Constrained conditions; Elbow muscles contributions; Endpoint stiffness; Endpoint stiffness properties generation; Externally imposed displacements; Hand; Mechanical interface; Movement control; Net mechanical properties; Posture control; Shoulder stability effects; Unconstrained trunk movements